Co-expression of Nisin Z and Leucocin C as a Basis for Effective Protection Against Listeria monocytogenes in Pasteurized Milk - Fu, Yuxin; Mu, Dongdong; Qiao, Wanjin; Zhu, Duolong; Wang, Xiangxiang; Liu, Fulu; Xu, Haijin; Saris, Per; Kuipers, Oscar P.; Qiao, Mingqiang (Frontiers in Microbiology, 2018)
Nisin, an important bacteriocin from Lactococcus lactis subsp., is primarily active against various Gram-positive bacteria. Leucocin C, produced by Leuconostoc carnosum 4010, is a class IIa bacteriocin used to inhibit the growth of Listeria monocytogenes. Because two bacteriocins have different modes of action, the combined use of them could be a potential strategy for effective inhibition of foodborne pathogens. In this study, L. lactis N8-r-lecCI (N8 harboring lecCI gene) coexpressing nisin–leucocin C was constructed based on the food-grade carrier L. lactis N8. Production of both bacteriocins was stably maintained. Antimicrobial measurements showed that the recombinant strain is effectively against Listeria monocytogenes and Staphylococcus aureus and moderately against Salmonella enterica serovar Enteritidis and Escherichia coli because of its stronger antibacterial activity than the parental strain, this result first demonstrated that the co-expression of nisin and leucocin C results in highly efficient antimicrobial activity. The checkboard assay showed that the antibacterial activity of L. lactis N8-r-lecCI supernatant was enhanced in the presence of low concentration of EDTA. Analysis of the scanning electron microscope image showed the biggest cellular morphology change in L. monocytogenes treated with a mixture of EDTA and L. lactis N8-r-lecCI supernatant. The practical effect was verified in pasteurized milk through time-kill assay. The L. lactis N8-r-lecCI strain expressing both nisin and leucocin C has a promising application prospect in pasteurized milk processing and preservation because of its strong antibacterial activity.